Humova pýcha a její výklad u Gabriely Taylorové - Hynek Janoušek (Reflexe, 2025)
The text first briefly outlines the use of Hume’s concept of pride in Taylor’s Book Pride, Shame, and Guilt. Emotions of Self-Assessment. This is followed by a distinction between the emotion of pride and pride belonging to high social status in Taylor, including an explanation of why it is still relevant today. We then present an interpretation of the five constraints on the cause for the emotion of pride in Hume and in Taylor and offer our own “Humean” reflection on Taylor’s critique of Hume. In an interpretation of the fifth constraint on pride at the end of the article, the reader findsan outline of a possible explanation of how Hume might have conceived of the conjunction of these two meanings of pride. Furthermore, in discussing Hume’s constraints of pride we deal with the difficulties involved in Hume’s theory of value in particular. In doing so, we conclude that Hume, had he not abandoned his original idea of revising the Treatise of Human Nature for a second edition, would have had to expand his limitation on the value of the object of pride considerably.